On Plastic Design of Rotating Discs of Finite Thickness - Zowczak, W. (Engineering Transactions, 1984)
A new method of plastic design of axially-symmetric rotating discs is proposed. The method of characteristics, known from the mechanics of plastic flow, has been used to construct statically admissible stress. fields and thus to find safe profiles of designed discs. The equations of characteristics derived for the case under consideration differ only slightly from the ones for the standard axially-symmetric case. The derived equations have been used to calcu1ate examples of safe profiles of rotating discs for different values of rotational speed.